Small Talk Among the Indonesians in Three Different Countries: America, Indonesia, Philippines - Katemba, Caroline Victorine (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2016)
This study explores the “Small Talk” Among the Indonesians in three countries. It aims to determine the topics that make up a small talk among the Indonesians in the motherland/homeland, USA (New Jersey, LA, Washington D.C), and the Philippines (Manila).This study sought to answer the following questions: (a) What particular topics of conversation shared by the Indonesians upon meeting for the first time? (b). Are Indonesians who stay in the motherland/homeland and those who are in the Philippines and those who migrated to the USA shared the same topics? (c).What changes of conversational topic has taken place? Keywords: small talk, Indonesian culture, the Indonesians